Revista ACB Vol. 16, n. 2 (2011) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Revista ACB Vol. 16, n. 2 (2011)Link de acesso ao númerohttp://revista.acbsc.org.br/index.php/racb/issue/view/47